Cynara scolymus (artichoke) and its efficacy in management of obesity - Mohaddese Mahboubi (Faculty of Pharmacy, Cairo University, 2018)
Obesity, the most prevalent metabolic disorder is associated with elevated body fat mass and body mass index. Cynara scolymus L. is famous for its hepatoprotective properties, also it seems to have good potency as anti-obese agent. In this review article, the potency of C. scolymus as anti-obese agent has been evaluated. The evidences based information were extracted from accessible international electronic databases (PubMed, Springer, Science Direct, Wiley and Google), and books (Persian or English), by key word of Cynara scolymus and artichoke plus obesity or the mechanism of anti-obese drugs. C. scolymus inhibits the digestive enzymes such as pancreas lipase, α-amylase, α-glucosidase, increases the bile secretion, inhibits of inflammation and ROS, improves liver function, gut microbiota, enhances lipolysis and lipid metabolism, and reduces blood glucose in preclinical and clinical studies. Designing large multi-center clinical trials on C. scolymus and evaluating its effects on weight loss in comparison with famous drug such as orlistate could be the subject of future studies. Keywords: Cynara scolymus, Obesity, Lipolysis, Lipase, Artichoke